Corrosion Behavior of Q235 Steel and Hot-Dip Galvanized Steel in Brown Soil Environment - YAO Xin, CHEN Hao, ZHOU Xuejie, WANG Jingyu, YU Jianfei, ZHANG Ming, WU Jun, CHEN Zhijian (Cailiao Baohu)
In order to study the initial soil corrosion behavior of Q235 steel and hot-dip galvanized steel， which are commonly used metallic materials for grounding grid equipment， in a brown loam soil environment， four soil corrosion experimental sites-both inside and outside of Dongjin and Qiaoying stations were chosen in the Xiangyang area of Hubei province.Macro-morphological analysis，micro-morphological analysis，corrosion product analysis and electrochemical testing were employed to analyze the specimens.The morphology analysis results showed that the surface of the carbon steel sample corroded for 1 a in the soil environment of Xiangyang was non-uniform corrosion with obvious pockmarked corrosion pits visible， while the galvanized steel material exhibited no obvious red rust without the obvious damage on the surface galvanized layer.The analysis of corrosion products showed that the brown soil in Xiangyang area was an alkaline soil with high moisture content.The main components of the rust layer on the surface of Q235 steel soil buried sample 1 a were iron oxides and trace amounts of SiO2， while the corrosion products on the surface of galvanized steel were mainly zinc oxides and trace amounts of SiO2.The correlation analysis between corrosion rate and soil physicochemical properties displayed that in the soil environment of Xiangyang， the corrosion rate of the two samples was positively correlated with soil physicochemical properties.Specifically， the soil pH value had the most significant impact on soil corrosion rate.The electrochemical results indicated that the galvanized layer on the surface of galvanized steel provided good protection for the substrate， and the corrosion current density of galvanized steel was 1～2 orders of magnitude lower than that of Q235 steel.Overall， galvanized steel materials exhibited superior corrosion resistance compared to Q235 steel materials in the brown soil environment of Xiangyang region.Notably，the pH of the local soil had a major impact on the galvanized steel material’s rate of corrosion in the soil.